Clinical and metabolic effects of aminophosphonate therapy in children with heart rhythm disturbances - Olga V. Senatorova; Elena B. Khramova; Vadim A. Kuznetsov; Oksana I. Sergeychik (Бюллетень сибирской медицины, 2017)
The aim of the survey is to summarize and assess a number of studies that examined the clinical and metabolic effects of aminophosphonates, particularly dimephosphon, which possess antioxidant and membrane-stabilizing effects. This paper presents a differential effect of dimephosphon on cell membrane functional activity as well as on structural features of platelet membrane as a model of smooth muscle cell in combined therapy in children with different clinical varieties of sick sinus syndrome.